2012
DOI: 10.1089/apc.2011.0278
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Gender Differences in Efficacy Outcomes for HIV-Positive Subjects in Randomized Controlled Clinical Trials of Antiretroviral Therapy (2000–2008)

Abstract: Women are often underrepresented in randomized clinical trials (RCT) of HIV-1 drugs. As a result, determining whether women have different virologic outcomes compared to men is not always possible because the gender-related analyses usually lack statistical power. To address this important public health concern, the Food and Drug Administration's (FDA) Division of Antiviral Products (DAVP) created a database including 20,328 HIV-positive subjects from 40 RCTs in 18 New Drug Applications (NDAs) submitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 17 publications
4
69
2
Order By: Relevance
“…Of note, between 2007 and 2009, three new HIV drugs were approved by the FDA, with an average of 12% women participating in the LPCTs of these drugs. The data indicated that participation of women in HIV drug trials is low (12%) and has decreased compared with the 20% that was reported for randomized controlled clinical trials of antiretroviral therapy products approved by the FDA from 2000 to 2008 by Soon et al,19 and the participation rate is lower than the disease prevalence; in 2008, the CDC reported that women make up 25% of HIV patients living in the United States. 20 Although gout is a disease that predominately affects men, disease prevalence in women has increased in the last few decades, and a 2004 study reported that about 30% of the patients are women.…”
Section: Participation Of Women In Nda Late-phase Clinical Trialsmentioning
confidence: 91%
“…Of note, between 2007 and 2009, three new HIV drugs were approved by the FDA, with an average of 12% women participating in the LPCTs of these drugs. The data indicated that participation of women in HIV drug trials is low (12%) and has decreased compared with the 20% that was reported for randomized controlled clinical trials of antiretroviral therapy products approved by the FDA from 2000 to 2008 by Soon et al,19 and the participation rate is lower than the disease prevalence; in 2008, the CDC reported that women make up 25% of HIV patients living in the United States. 20 Although gout is a disease that predominately affects men, disease prevalence in women has increased in the last few decades, and a 2004 study reported that about 30% of the patients are women.…”
Section: Participation Of Women In Nda Late-phase Clinical Trialsmentioning
confidence: 91%
“…2,3 Between 2000 and 2008, only 15% of treatment-experienced patients enrolled in the 18 randomized controlled trials of HIV drugs submitted for approval to the Food and Drug Administration (FDA) were women. 3 Women of color have been particularly under-represented, despite the fact that they comprise a large portion of new infections.…”
mentioning
confidence: 99%
“…2,3 Between 2000 and 2008, only 15% of treatment-experienced patients enrolled in the 18 randomized controlled trials of HIV drugs submitted for approval to the Food and Drug Administration (FDA) were women. 3 Women of color have been particularly under-represented, despite the fact that they comprise a large portion of new infections. 4,5 In addition to HIV-related stigma, women of color may face both sex-based and race-based discrimination, culminating in increased rates of mental health issues.…”
mentioning
confidence: 99%
“…During the phase III trials and in postmarketing surveillance and studies, the pharmacokinetics and treatment responses of long-acting ART must be studied in adequate numbers of women for sex-stratified results to be presented [5658]. Studies in children and in pregnant and breastfeeding women will be important to extend the benefits of these agents to these key populations.…”
Section: Knowledge Gapsmentioning
confidence: 99%